Can Therapeutic Exercise Slow Down Progressive Functional Decline in Patients With Amyotrophic Lateral Sclerosis? A Meta-Analysis - Park, Donghwi; Kwak, Sang Gyu; Park, Jin-Sung; Choo, Yoo Jin; Chang, Min Cheol (Frontiers in Neurology, 2020)
Background: Despite the high incidence of muscle weakness in patients with amyotrophic lateral sclerosis (ALS), the effects of therapeutic exercise on these individuals have not been clearly determined. Methods: A comprehensive database search was conducted on PubMed, Embase, Cochrane Library, and SCOPUS. We included studies published up to December 31, 2019 that fulfilled our inclusion and exclusion criteria. Functional status was determined as the Amyotrophic Lateral Sclerosis Functional Rating Scale (ALSFRS) score (previous and revised versions) before and after a therapeutic exercise program for the meta-analysis. The Cochrane Collaboration’s tool for assessing risk of bias in randomized trials was used for the methodological quality assessments of included studies. The meta-analysis was performed using the RevMan v.5.3. Results: A total of 94 patients in the experimental group (who received therapeutic exercise) and 159 patients in the control group (who received conventional exercise or therapy) were included from five randomized controlled trials. The decrement of ALSFRS (previous version), ALSFRS-R (revised version), and ALSFRS-R-Respiratory scores at the 6-month evaluation were less for the therapeutic exercise group as compared to the control group. However, at the 6-month evaluation, the ALSFRS-R-Limb scores did not significantly differ between the two groups. Conclusions: Therapeutic exercise appears beneficial for patients with ALS. Further, it appears to exert more of a cardiopulmonary benefit, as opposed to preventing the progression of limb weakness. However, as the therapeutic exercises applied in each included study were not uniform, the result of our meta-analysis should be considered cautiously.